Вимоги до судді в Україні - Юшкевич, О. Г.; Iushkevych, O. G.; ORCID: http://orcid.org/0000-0003-0024-6070 (Адміністративне право і процес. – 2016. ‒ № 1 (15). - С. 157‒164, 2016)
У статті автор сформував вимоги до професійного судді в Україні, основу яких становлять знання, навички та вміння особистості, що займає посаду судді в Україні. Визначено сфери діяльності судді та перераховано конкретні знання, навички та уміння, якими має володіти суддя. Запропоновано шляхи вдосконалення поведінки суддів.

In the article the author defined demands to professional judges in Ukraine, based on knowledge, skills and competences of the person, applying for a position of a Judge in Ukraine. Author stressed in the article, that most of the judges have forgotten or just disregard the main principles of the judicial branch. Among of them author underlined, that they should grant trust of the society to the judicial system and also to the image of the judicial system, that plays the main role in the present-day society; and that judges, as individuals have to hold their positions as the respected ones, providing necessary level of the trust to them by the society, as they have to work hard to support and further develop the trust to the judiciary.

В статье автор сформировал требования к профессиональному судье в Украине, основу которой составляют знания, навыки и способности личности, который занимает должность судьи в Украине. Определены сферы деятельности судьи и перечислено конкретные знания, навыки и умения, которыми должен обладать судья. Предложены пути совершенствования поведения судей.
Demands to a judge in Ukraine
Требования к судье в Украине
Юшкевич О. Г. Вимоги до судді в Україні / Юшкевич Олена Геннадіївна // Адміністративне право і процес. – 2016. ‒ № 1 (15). - С. 157‒164.
Keywords: вимоги до судді; судьи; Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; довіра до суду; професійні риси; особистісні риси; професійна етика; судді; доверие к суду; профессиональные качества; личностные качества; профессиональная этика; judge; judge behavior; trust to the judge; professional features of a judge; personal features of a judge; psychology of a judge; ethics of a judge